Systematic Review and Meta-Analysis of the Efficacy and Safety Profile of Belimumab in Combination with Standard Therapy for Adults with Systemic Lupus Erythematosus - Dharmawan, Mochamad Rangga Alif; Rochmanti, Maftuchah; Awalia; Wungu, Citrawati Dyah Kencono (Universitas Airlangga, 2025)
Introduction: Systemic lupus erythematosus (SLE) is a multi-system autoimmune disorder marked by pathogenic autoantibodies, resulting in considerable morbidity and mortality. Despite existing diverse treatment regimens, the need for more effective therapies persists. Recent advancements include monoclonal antibodies, such as belimumab, which can inhibit receptors tied to SLE’s pathogenesis. This meta-analysis aimed to evaluate the efficacy and safety of combining belimumab and standard therapy compared to placebo in SLE patients, utilizing as many indicators as possible to comprehensively assess the former's potential. Methods: This study adhered to the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) and the Cochrane Handbook for Systematic Reviews of Interventions. A thorough literature search was performed across various databases, including PubMed, ScienceDirect, ProQuest, and grey literature sources such as MedRxiv and BioRxiv. The data underwent statistical analysis, with I²<50% indicating low heterogeneity and p<0.05 denoting statistical significance. Results: The literature search yielded seven records for analysis in this study. All the selected studies were multicenter, phase III/IV, randomized clinical trials published between 2011 and 2019. The selected studies' risk of bias was assessed using Cochrane’s Risk of Bias (RoB) 2 tool. The results indicated that belimumab and standard therapy significantly improved disease activity, reduced flare occurrences—particularly severe flares, lowered corticosteroid dosage, and enhanced key biomarkers compared to placebo. The safety profile was favorable, with significantly minimal side effects, infections, and mortality risks. Conclusion: Belimumab combined with standard therapy demonstrates promising efficacy and safety for SLE treatment, suggesting its potential for broader adoption in clinical practice. Highlights: 1. This systematic review and meta-analysis provide a thorough and complete analysis of multiple indicators regarding the efficacy and safety of belimumab in the treatment of systemic lupus erythematosus (SLE), which have never been reviewed before. 2. The findings of this study may lead to broader acceptance and adoption of belimumab as the standard treatment for SLE.